2022
DOI: 10.3892/ol.2022.13608
|View full text |Cite
|
Sign up to set email alerts
|

FXR1 promotes proliferation, invasion and migration of hepatocellular carcinoma in vitro and in vivo

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy that is associated with a poor prognosis. The extensively studied TGF-β pathway is mediated by SMAD proteins. FXR1, a protein-coding gene belonging to the fragile X-related (FXR) family, is involved in the TGF-β pathway. Previous studies have shown that FXR1 promotes the proliferation, invasion, and migration of colorectal cancer cells. The aim of the present study was to explore the effects of FXR1 on HCC via the TGF-β/SMAD signaling pathway. Immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…NDRG1 can enhance the interaction between fibroblasts and tumor cells, leading to the development of hepatocellular carcinoma [30,31]. FXR1 can promote the proliferation, invasion, and migration of hepatocellular carcinoma, and its action is mediated by Smad2/3 [32]. These studies provide additional evidence for the reliability of the genes we screened and are consistent with our predicted results.…”
Section: Discussionsupporting
confidence: 87%
“…NDRG1 can enhance the interaction between fibroblasts and tumor cells, leading to the development of hepatocellular carcinoma [30,31]. FXR1 can promote the proliferation, invasion, and migration of hepatocellular carcinoma, and its action is mediated by Smad2/3 [32]. These studies provide additional evidence for the reliability of the genes we screened and are consistent with our predicted results.…”
Section: Discussionsupporting
confidence: 87%
“…Our verification of FXR1 overexpression in numerous types of tumors, with some results corroborated by previous studies, supports this perspective. [6,[14][15][16] The prognostic implications and potential impact on tumorigenic processes of FXR1 expression levels in various human cancers remain unexplored and necessitate additional research. To our knowledge, this study represents the inaugural comprehensive examination of FXR1's expression and biological functionality from a pan-cancer viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…[55] In the context of hepatocellular carcinoma, FXR1 has been established as a factor that stimulates cell growth, movement, and infiltration by influencing the participation of SMAD2/3 in the TGF-β pathway. [15] Additionally, FXR1 expression has been directly linked to the survival and proliferation of cancer cells, as it facilitates the cyclization of cMYC mRNA and promotes the recruitment of eukaryotic translation initiation factors to translation initiation sites, thereby elevating cMYC levels in cancer cells. [4] Nowadays, an increasing number of studies have demonstrated the critical role of the immune microenvironment in the development and progression of tumors.…”
Section: Discussionmentioning
confidence: 99%